Difference between revisions of "022 Exam 2 Sample B, Problem 5"
Jump to navigation
Jump to search
(Created page with "<span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^2x + 1}\, dx.</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations...") |
|||
(6 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
− | <span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^2x + 1}\, dx.</math> | + | <span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx.</math> |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
Line 22: | Line 22: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |Use a ''u''-substitution with <math style="vertical-align: -8%">u = e^{ | + | |Use a ''u''-substitution with <math style="vertical-align: -8%">u = e^{2x}+1.</math> This means <math style="vertical-align: 0%">du = 2e^{2x}\,dx</math>. After substitution we have |
::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx\,=\, \int \frac{1}{u}\,du.</math> | ::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx\,=\, \int \frac{1}{u}\,du.</math> | ||
|} | |} | ||
Line 32: | Line 32: | ||
|- | |- | ||
| | | | ||
− | ::<math>\int\frac{1}{u}\,du\,=\, \ | + | ::<math>\int\frac{1}{u}\,du\,=\, \ln(u).</math> |
|} | |} | ||
Line 38: | Line 38: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | | Now we need to substitute back into our original variables using our original substitution <math style="vertical-align: - | + | | Now we need to substitute back into our original variables using our original substitution <math style="vertical-align: -8%">u = e^{2x} + 1</math> |
|- | |- | ||
− | | to find <math>\ | + | | to find <math style="vertical-align: -20%">\ln(u) = \ln(e^{2x} + 1).</math> |
|} | |} | ||
Line 46: | Line 46: | ||
!Step 4: | !Step 4: | ||
|- | |- | ||
− | |Since this integral is an indefinite integral we have to remember to add a constant  <math style="vertical-align: | + | |Since this integral is an indefinite integral we have to remember to add a constant  <math style="vertical-align: 1%">C</math> at the end. |
|} | |} | ||
Line 53: | Line 53: | ||
|- | |- | ||
| | | | ||
− | ::<math>\int \frac{2e^{2x}}{e^2x + 1}\, dx \,=\, \ | + | ::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx \,=\, \ln(e^{2x}+1) + C.</math> |
|} | |} | ||
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']] | [[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 12:01, 18 May 2015
Find the antiderivative of
Foundations: |
---|
This problem requires two rules of integration. In particular, you need |
Integration by substitution (u - sub): If is a differentiable functions whose range is in the domain of , then |
|
We also need the derivative of the natural log since we will recover natural log from integration: |
|
Solution:
Step 1: |
---|
Use a u-substitution with This means . After substitution we have
|
Step 2: |
---|
We can now take the integral remembering the special rule: |
|
Step 3: |
---|
Now we need to substitute back into our original variables using our original substitution |
to find |
Step 4: |
---|
Since this integral is an indefinite integral we have to remember to add a constant at the end. |
Final Answer: |
---|
|